Adolescents’ jobs and the course of dermatitis symptoms throughout puberty - Radon, Katja; Riu, Elena; Dressel, Holger; Windstetter, Doris; Weinmayr, Gudrun; Weiland, Stephan; Vogelberg, Christian; Scharrer, Eva Maria; Leupold, Wolfgang; von Mutius, Erika; Nowak, Dennis (Scandinavian Journal of Work, Environment & Health, 2006)
' ' OBJECTIVES ': 'This study evaluated the course of dermatitis symptoms throughout puberty taking into account occupational exposures in a population-based study. ' ' METHODS ': 'Participants enrolled in the ISAAC-II (International Study of Asthma and Allergies in Childhood) study in Munich and Dresden in 1995 and 1996 were sent a postal questionnaire in 2002 (age at follow-up 16 to 18 years). The questionnaire included items on atopic diseases, jobs, including holiday jobs and vocational training, and potential confounders. The most recent of the adolescents’ jobs held for at least 8 hours a week, and for at least 1 month, were coded according to the ISCO-88 system. ' ' RESULTS ': 'Overall, data of 3785 adolescents were included in the analyses. The incidence of dermatitis symptoms during puberty among those without such symptoms at baseline was 7%. Altogether 31% of the participants reported an employment history. Those already employed were more likely to report a new onset of dermatitis symptoms. Jobs associated with a new onset of symptoms were work in the health care sector, vocational training in bakeries, and cleaning. The first 9 months of exposure were particularly relevant for new cases of dermatitis symptoms (odds ratio 3.7, 95% confidence interval 1.5–9.6). ' ' CONCLUSIONS ': 'Early occupational exposure is associated with the development of symptoms of dermatitis. The types of skin alterations need to be assessed in the next stage of the study.
Keywords: adolescent; atopic dermatitis; cohort study; contact dermatitis; contact urticaria; International Study of Asthma and Allergies in Childhood; occupational allergy risk; occupational medicine; puberty